PENGARUH LITERASI EKONOMI, LITERASI KEUANGAN, DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA PENDIDIKAN EKONOMI FAKULTAS EKONOMI DAN BISNIS UNIMED - Anggi Emalia Putri; Saidun Hutasuhut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of economic literacy, financial literacy, and entrepreneurial knowledge on entrepreneurial intention among students of the Economics Education Study Program, Faculty of Economics, Universitas Negeri Medan, Cohort 2021–2022. This research employed a quantitative approach using a survey method. The population consisted of students of the Economics Education Study Program from the 2021–2022 cohort, with a sample of 105 respondents. Data were collected through questionnaires and documentation. The data were analyzed using multiple linear regression with the assistance of SPSS. The results showed that economic literacy had a positive and significant effect on entrepreneurial intention, with a regression coefficient of 0.168 and a significance value of 0.000. Financial literacy also had a positive and significant effect on entrepreneurial intention, with a regression coefficient of 0.091 and a significance value of 0.000. Furthermore, entrepreneurial knowledge had a positive and significant effect on entrepreneurial intention, with a regression coefficient of 0.247 and a significance value of 0.000. Entrepreneurial knowledge was found to have the strongest influence compared with economic literacy and financial literacy. Simultaneously, economic literacy, financial literacy, and entrepreneurial knowledge had a positive and significant effect on students’ entrepreneurial intention. Therefore, improving students’ understanding of economics, financial management skills, and entrepreneurial knowledge can contribute to strengthening their intention to become entrepreneurs.